Nuancing maritime security governance in the Straits of Malacca: a comparative analysis on Indonesia, Malaysia, and Singapore - Sumathy Permal; Ravichandran Moorthy (Penerbit UKM, 2024)
Indonesia, Malaysia, and Singapore are littoral states of the Straits of Malacca (SOM), the world’s busiest waterway connecting the Indian and Pacific oceans, with around 80,000 ships passing through this route annually. While maritime security governance of this waterway is a serious concern especially to those states, their responses to it has differed particularly in regard to three security mechanisms: the Proliferation Security Initiative (PSI), the Malacca Straits Patrol (MSP), and the Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia (ReCAAP). The states’ approaches can be viewed primarily through the lens of sovereign interests, economic interests, and legal obligations. In addition, the role of institutions appears as an intervening factor influencing their responses. This article first analyses maritime security governance and examines why it has garnered much attention in contemporary international relations. Second, it assesses the importance of the SOM as a strategic location, a critical trading route since ancient times, as well as the value it holds for international shipping. Third, it examines the littoral states’ responses to maritime security governance, focusing on the factors influencing them. The article finds that their responses to external power security initiatives differ compared to the indigenous security mechanism in the SOM. Despite that, the underlying theme among the three states is to uphold their obligations as coastal states as provided under UNCLOS and in cooperating with each other and international users, though several caveats do seem to also apply.